Effect of phosphorous groups on the stabilization and activation of low-cost lignin fibers prepared by electrospinning - Berenguer-Betrián, Raúl; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2013)
The feasible wider use of carbon fibers in many of their current and potential applications demands a reduction of their manufacturing costs. In this sense, the use of lignin as an abundant, renewable and low-cost carbonaceous precursor and a simple and versatile production technique, such as the electrospinning, represents an advantageous and promising approach [1-3]. Particularly, the devIlopment of high-value co-products from lignocellulosic biomass-derived industries, such as biorefineries and pulp and paper mills, could suppose a significant opportunity to reduce their associated costs and environmental impacts. However, the use of lignin itself in the production of carbon fibers requires of successive stabilization and carbonization steps that currently slow down, raises the price and, therefore, limits their commercialization and industrial application. In this work, a new method to produce novel sub-micrometer carbon fibers by electrospinning of phosphorous-containing lignin solutions is proposed.
Keywords: Fibras de carbono; Lignin; Carbon fibers; Electrospinning; Phosphoric acid